Validation of the NOVA score for the consumption of ultra-processed foods by young women of Medellín, Colombia (2023)
ABSTRACT: Ultra-processed foods (UPFs) are associated with deterioration in dietary quality and the development of chronic diseases. The NOVA score, developed in Brazil to assess UPF consumption quickly and inexpensively, is adapted and validated here using a sam- ple of 203 young women from Medellín, Colombia. Food consumption was evaluated using 24-hour dietary recall and with the NOVA-UPF score. Food items were classified using the NOVA categories. The energy consumed from UPFs and its percentage of the total energy consumed was estimated. The association between the NOVA-UPF score and the percentage of energy from UPF (%UPF/E) was evaluated. Both vari- ables were categorized into quintiles and concordance was estimated using prevalence and bias-adjusted kappa (PABAK). A regression model was used to assess the associa- tion between the NOVA-UPF score and critical nutrients. The mean NOVA-UPF score among study participants was 4.5, with 27% of the total energy they consumed com- ing from UPFs. There was a positive, linear association between the NOVA-UPF score and %UPF/E (p < 0.001) and substantial agreement (PABAK = 0.75) in the classifica- tion of participants between UPF energy quintiles and NOVA-UPF score quintiles. The NOVA-UPF score was positively and significantly associated with sodium, total fat, and saturated fat intake. We conclude that the adapted NOVA-UPF score may help monitor the consumption of UPFs among young women in Medellín.